Risk factors for hemorrhage in patients with long-term aspirin therapy undergoing emergency external ventricular drainage/intracranial pressure probe placement - Fei Gao; Shunnan Ge; Wenxing Cui; Jingya Zhao; Yang Yang; Wei Guo; Hao Bai; Bao Wang; Chen Yang; Shijie Mu; Liang Wang; Tianzhi Zhao; et al. (Heliyon, 2024)
Background: Studies have been inconclusive on the risk for hemorrhage in patients with a history of aspirin use who underwent emergency external ventricular drainage (EVD)/intracranial pressure (ICP) probe placement. The aim of this study was to explore hemorrhage-related risk factors in order to reduce the risk for hemorrhage in these patients. Methods: Between July 2014 and July 2020, patients were retrospectively divided into EVD/ICP-related hemorrhage and non-hemorrhage groups. The collected data included age, gender, major diagnosis, medical history, imaging examinations, conventional coagulation test data, thromboelastography with platelet mapping (TEG-PM), surgical procedures and discharge conditions. Results: In total 94 patients, 21 in the hemorrhage group (15 males, 6 females) and 73 in the non-hemorrhage group (52 males, 21 females) were included. The majority of hemorrhages were recorded in EVD patients (19/21; 90.5%). Platelet AA pathway inhibition rate of ≥75% (sensitivity: 79.45% specificity: 52.38%) (P = 0.014) and SBP ≥125 mmHg (P = 0.006) were significantly related to hemorrhage. When the platelet AA pathway inhibition rate was ≥75% and the during-procedure SBP was ≥125 mmHg, the hemorrhage rate was significantly higher (83.3%) than with SBP <125 mmHg (6.7%) (P < 0.001). When the inhibition rate was <75%, there were no significant differences in the hemorrhage rates between the during-procedure SBP ≥125 mmHg group (17.2%) and the SBP <125 mmHg group (13.2%) (P > 0.05). Multivariate logistic regression analysis revealed that a platelet AA pathway inhibition rate ≥75% (OR = 5.183, 95% CI: 1.683–15.960) and during-procedure SBP ≥125 mmHg (OR = 4.609, 95% CI: 1.466–14.484) were independent risk factors for EVD/ICP-related hemorrhage. Conclusion: Patients with long-term aspirin therapy, a platelet AA pathway inhibition rate ≥75% and during-procedure SBP ≥125 mmHg had a significantly higher risk of hemorrhage, which could be reduced by adjusting the SBP to <125 mmHg.